2013
DOI: 10.3176/oil.2013.2s.12
|View full text |Cite
|
Sign up to set email alerts
|

Mine Water as a Potential Source of Energy From Underground Mined Areas in Estonian Oil Shale Deposit

Abstract: Underground oil shale mining has been applied for ninety years inEstonian deposit in the middle-north part of Baltic oil shale deposit. The underground mining method of oil shale creates underground free space and the mine workings are filled with water after closure, which makes issues of land stability topical.Underground water pools or technogenic water bodies with all-the-yearround stable temperature are formed in the filled underground of oil shale mines. These water bodies have a potential for use as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Some studies [10][11][12] have shown that from a biodiversity perspective it is best when areas are left for nature to take over. The potential usage of underground mined areas in Estonian oil shale deposits has also been investigated [13,14]. The question today is how to proceed when there is a need to foster regional development and afforestation is far from proper managing.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [10][11][12] have shown that from a biodiversity perspective it is best when areas are left for nature to take over. The potential usage of underground mined areas in Estonian oil shale deposits has also been investigated [13,14]. The question today is how to proceed when there is a need to foster regional development and afforestation is far from proper managing.…”
Section: Introductionmentioning
confidence: 99%
“…To utilize total dry OSA as concrete for backfilling or road basement will require working out mixes of OSA, which would be able to harden concrete and make it durable in exposure conditions [10]. Low temperature and presumptive contact with water in the early period of hardening are challenges for OSA concrete to meet.…”
Section: Introductionmentioning
confidence: 99%